DEINDUSTRIALISASI SEBUAH ANCAMAN KEGAGALAN TRIPLE TRACK STRATEGY PEMBANGUNAN DI INDONESIA - Prasetyo, P. Eko (Semarang State University, 2011)
SBY government work effort through the triple-track strategy namely pro-growth, pro jobs and pro-poor developments will be doomed to fail because of a deindustrialization inIndonesia. The phenomenon of deindustrialization is characterized by the continued decline of industrial contribution mainly manufacture industrial sektor to the value added, employment, exports and contribution to GDP growth, would obviously be a serious threat to the government in its efforts to achieve economic growth to reduce unemployment and poverty. Industrial sektor at this time was no longer regarded as a leading sektor in the national and regional development, so that if eagerly handled will have a negative impact more and could threaten the stability of the economic development of Indonesia.